Employment of young people with mental health conditions: making it work. Issue 10 (8th May 2022) - Subramaniam, Mythily; Zhang, Yunjue; Shahwan, Shazana; Vaingankar, Janhavi Ajit; Satghare, Pratika; Teh, Wen Lin; Roystonn, Kumarasan; Goh, Chong Min Janrius; Maniam, Yogeswary; Tan, Zhuan Liang; Tay, Benjamin; Verma, Swapna; et al.
Abstract: Purpose: The current study was undertaken to understand and describe the meaning of work as well as the barriers and facilitators perceived by young people with mental health conditions for gaining and maintaining employment. Materials and Methods: Employing a purposive and maximum variation sampling, 30 young people were recruited and interviewed. The respondents were Singapore residents with a mean age of 26.8 years (SD = 4.5, range 20–34 years); the majority were males (56.7%), of Chinese ethnicity (63.3%), and employed (73.3%), at the time of the interview. Verbatim transcripts were analysed using inductive thematic analysis. Results: Three global themes emerged from the analyses of the narratives, which included (i) the meaning of employment, (ii) barriers to employment comprising individual, interpersonal and systemic difficulties and challenges participants faced while seeking and sustaining employment and (iii) facilitators of employment that consisted of individual and interpersonal factors that had helped the young persons to gain and maintain employment. Conclusions: Stigma and discrimination emerged as one of the most frequently mentioned employment barriers. These barriers are not insurmountable and can be overcome both through legislation as well as through the training and support of young people with mental health conditions. IMPLICATIONS FOR REHABILITATION: Employment offers several benefits to people with mental health conditions, including improvement in economic status, self-efficacy, and empowerment. Stigma is a significant barrier to employment for young people with mental health conditions; remaining optimistic about career prospects and getting support from peers is vital to employment success. Disclosure of the mental health condition at the place of work is beneficial to the person's own recovery and helpful to others; however, young people must be empowered to choose when and what they want to disclose and under what circumstances. Families help young people with mental health conditions in achieving their employment goals by offering emotional and instrumental support, as well as motivating them to accomplish more.